Announcement system using wap over bluetooth / Azhan Ezra Abdul Aziz - Abdul Aziz, Azhan Ezra (Faculty of Information Technology and Quantitative Sciences, 2006)
This paper concentrates on the study of using Bluetooth wireless technology as a physical link to WAP services. Currently, Bluetooth technology are use to connect several devices and peripherals together. WAP services are a service provider dependent service and there are cost associates to use it. Implementing the proposed system will provide an opportunity to have an interesting system to be studied and explored as it has numerous potential. This project mainly focuses on developing a method to provide mobile phone users an access to a WAP site without no cost similarly like a laptop users browsing the internet using free public hotspots. Numerous programming languages have been used throughout the project such as WML and Visual C++. Several aftermarket software products have also been used in order to make the system feasible. In the end of the development, the prototype for the system has been completed and ready to be tested. In this project, only a single mobile phone model can be tested due to limited funding. This thesis actually provides an initial small step that can be used to explore a lot of possible interesting applications when appropriate time and financial resources can be provided.